Isolation and Culture of Spinal Cord Motor Neurons. Issue 1 (2nd March 2015) - Klausmeyer, Alice; Stern, D.; Wiese, S.
Abstract: Isolated spinal motoneurons are a powerful tool for studying basic mechanisms of neurite growth and survival. Since motoneurons are a minor population of developing spinal cord cells, they need to be purified and enriched to separate them from non‐neuronal cells. Therefore, the particular feature of embryonic motoneurons to express the low affinity neurotrophin receptor p75 NTR is used to separate the motoneurons from other contaminating cells. Two ways are described to isolate embryonic motoneurons: the basic protocol taking advantage of the ability of p75 NTR to bind lectin, and an alternative method using an antibody against p75 NTR for a panning procedure. These protocols comprise suggestions for the cultivation of the isolated motoneurons for experiments regarding neural outgrowth and survival as well as instruction for the preparation of proteins of the cells. © 2015 by John Wiley & Sons, Inc.